PLACENTA ACCRETION - Нонна Марковна Шибельгут; Наталья Анатольевна Батина; Полина Андреевна Овчарова; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Кира Борисовна Мозес; Вадим Гельевич Мозес (Medicina v Kuzbasse, 2023)
The ingrowth of the placenta into the scar on the uterus after the previous cesarean section (CPNM) refers to extremely serious complications of pregnancy and is one of the most acute and urgent problems of world obstetrics. There are three main approaches implemented during delivery of these patients: hysterectomy (simultaneous or delayed), organ-preserving surgery, as well as conservative management of patients against the background of cytostatics. However, the lack of an appropriate material and technical base, and in some cases, the clinical situation does not leave a choice in favor of organ-sparing delivery. The article presents a clinical case of placenta ingrowth into the scar after cesarean section.